Entusiast og bakstrever - Haugsbakk, Geir (Oplandske Bokforlag AS, 2025)
With tablets as door openers, Apple and Google conquered Norwegian classrooms and were met with great enthusiasm. Now the objections have arrived, also from the responsible authorities. But how could perfectly competent politicians be misled into believing in castles in the air and into adopting the advertising language of the tech giants?